Human Umbilical Cord Perivascular Cells Prevent Tumor Growth in a Melanoma Tumor-Bearing Mouse Model and Modulate Breast Cancer and Melanoma Cells in a Cell Line-Dependent Manner In Vitro - Lianet Lopez; Hannah Shuster-Hyman; Eden Marco; Hasna Khan; Avishai Gasner; Aleksandra Uzelac; Brandon Wyse; Poonam Mander; Mugundhine Sangaralingam; Joseph Fish; Ariel Gorodensky; Samar Mouazz; et al. (Stem Cells International)
First trimester (FTM) and term human umbilical cord perivascular cells are promising mesenchymal stromal cell candidates to mitigate side effects of oncotherapy, but their safety for cancer patients remains to be determined. This study was designed to determine if human umbilical cord perivascular cells modulate tumor growth when injected systemically in a tumor-bearing mouse model. Immunodeficient mice-bearing palpable subcutaneous SK-MEL-28 human melanoma tumors were randomized to receive a tail vein injection of three human umbilical cord perivascular cell lines resuspended in hank’s buffer saline solution (vehicle) or vehicle only, as a control. Fibroblast cells were included as a cell control in some experiments. Tumor size was monitored weekly and weighed at 3-weeks postinjection. Cell fate and tumor cell proliferation, apoptosis, vascularization as well as tumor-associated immune cells were assessed using immunostaining and flow cytometry. Serum tumor necrosis factor alpha and C-reactive protein levels were measured using enzyme-linked immunosorbent assays. Transwell coculture models were used to study the paracrine effects of multiple lines of human umbilical cord cells on human melanoma cell lines as well as breast cancer cell lines. Systemic administration of FTM and term human umbilical cord perivascular cells, but not fibroblast cells, prevented melanoma tumor growth in a tumor-bearing animal model by modulating tumor cell proliferation and systemic inflammatory mechanisms. Cancer cell- and donor-dependent paracrine effects on cancer cell growth were observed in vitro. Our preclinical studies thus suggest that, with regards to its effects on tumor growth, systemic administration of FTM and term human umbilical cord perivascular cells may be a safe cell therapy to address the side effects of cancer.